Model Pengembangan UMKM Berbasis Triple Helix: Tendensi Peran Akademisi Perguruan Tinggi - Terezia Valency Pattimahu; Novalien Carolina Lewaherilla; Gerrit Mathias Pentury (Departement of Mathematics Education, 2023)
The importance of the role of Triple Helix for the development of MSMEs is one of the bases for this research. By taking a location in Kairatu District, West Seram Regency (SBB), it is expected to be able to produce a Triple Helix Model in the development of MSMEs in Kairatu District. The type of research conducted is qualitative research using the questionnaire method with Triple helix actors, namely academics, business, and government, which play a role in the development of MSMEs in Kairatu District. As a result, a comprehensive study can be obtained in building an integrated Triple Helix Model in the development of MSMEs. The study results show that Kairatu Sub-district has the potential of MSMEs that can develop and be sustainable through the synergy of the Triple Helix elements of government, academia and business. The role of academics in higher education must continue to improve the quality and quantity of MSMEs to be competitive and survive in the present and future.